Responsible Education: an educational program in which emotions, relationships and creativity make a difference (Journal of Parents and Teachers, 2012)
This article sets out the program named Responsible Education that the Fundación Botín is being carrying out in Cantabria since 2004 with 100 centres, 776 teachers and 15.000 students and families with the main objective of supporting  and making easier for the children and young kids the difficult task of growing up healthily, physically, emotionally, intellectually and socially. This innovative program, that backed the idea of an emotional and social education being part of the school curriculum as a fully integrated factor, is being possible because of the collaboration of the Council of Education of the Government of Cantabria; the participation and commitment of many volunteers; the coordination of the initiatives of schools, families and community; the close follow-up from teachers; viability and transferability as well as the evaluations of actions with order and rigor. External evaluations made by University of Cantabria conclude that the program Responsible Education has manage to improve significantly the emotional intelligence and, also, the assertiveness of the students;  reducing at the same time their anxiety levels and achieving a positive correlation between school environment and academic performance. font-family:"Arial","sans-serif";mso-fareast-font-family:"Times New Roman"; mso-ansi-language:ES;mso-fareast-language:EN-US;mso-bidi-language:AR-SA; font-style:normal;mso-no-proof:yes'>Las personas que desarrollan sus fortalezas y capacidades, mejoran su calidad de vida y previenen la aparición de trastornos. Además, la percepción de eficacia y bienestar, aumentan al mismo tiempo que la motivación. Es por eso que nos parecen relevantes y porque aumentan la sensación de alegría. Los padres y maestros tenemos una gran responsabilidad de enfocarnos  más hacia las capacidades de nuestros hijos y alumnos, que hacía los déficits y limitaciones. Es un estilo que se aprende, y así ellos también ellos serán más hábiles en reconocer, utilizar y desarrollar sus fortalezas en el presente y también en el futuro.
Keywords: Teaching experience; innovation; emotion; creativity; evaluation.; experiences